Educating managers for the future - J. S. Goodwin; R. M. Fulmer (South African Journal of Business Management, 1985)
The authors predict that South Africa will need approximately 200 000 new executives within the next 15 years. Simultaneously the organizations will become more complex and difficult to manage. They suggest that the development of such a large number of managers within the black and white community will be difficult and furthermore, managers will also require new knowledge. Even highly trained professionals may quickly become obsolete unless they continue to receive further training and development. Future-oriented courses are already being developed and taught in a number of overseas universities. The authors suggest four approaches to this future orientation: studying of future trends and projections, coping with rapid change, impact analysis, and scenario writing.Die skrywers van hierdie artikel voorspel dat Suid-Afrika binne die volgende 15 jaar bykans 200 000 nuwe uitvoerende beamptes sal moet ontwikkel om aan die behoeftes van organisasies te voldoen. Terselfdertyd sal organisasies egter meer kompleks en moeilik bestudeerbaar word. Nie alleen sal die ontwikkeling van so 'n groot getal bestuurders problematies wees nie, maar bestuurders sal ook nuwe kennis benodig. Selfs hoogsopgeleide bestuurders sal vinnig onbruikbaar raak tensy hulle voortdurend aan nuwe opleiding en opvoeding blootgestel word. Toekomsgerigte curricula word alreeds aan verskeie oorsese universiteite ontwikkel en aangebied. Die skrywers stel vier benaderings tot hierdie toekomsgerigte opleiding voor: indringende studie van toekomstige tendense en voorspellings, metodes om tred te hou met veranderinge, impakanalise en die skryf van moontlike scenarios.
Keywords: 650